Transport for tomorrow engineering integrated solutions : Friday 19 June 1998 (Thomas Telford, 1998)
This title is part of the ICE Publishing complete digital collection - helping ensure access to essential engineering content from past to present. Proceedings of a joint conference with the Highways Agency held on 19 June 1998.